System Identification and active modal control of a flexible truss structure - Joventino, C. F. [UNESP]; Abreu, G. L.C.M. [UNESP]; Lopes, V. [UNESP] (ECCOMAS, 2015)
The aim of this paper is to illustrate the active control of vibration of a flexible truss structure using a model-based digital controller. The state-space model of the system is derived using a system identification technique known as the Observer/Kalman Filter Identification (OKID) method together with Eigensystem Realization Algorithm (ERA). Based on the measured response of the structure to a chirp input, an explicit state-space model of the equivalent linear system is determined. To reduce the vibrations caused by an impulse force, two active strut members are installed along a vertical of the base bay of the truss. The active strut element consists of a piezoelectric ceramic stack actuator, a force transducer and mechanical interfaces. An integral controller is designed to suppress vibration of the truss. The controller, formulated with the root locus approach, is designed to maximize modal damping of a constructed truss structure. Experimental results illustrate that the active piezoceramic strut actuators and the integral controller can effectively reduce vibration of the truss.
Keywords: Active control; Flexible structures; System identification